Nutmeg-Flavored Tea With Skin Health Advantaged Product To Empower Farmers In Hanau Berak Village, Pesawaran Regency - Suryaneta Suryaneta; Indah Puspita Sari; Tikarahayu Putri; Iwan Syahjoko Saputra; Achmad Gus Fahmi (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
: This article introduces a community service conducted by the PkM ITERA team in Hanau Berak Village, Pesawaran Regency, Lampung. Nutmeg, being a primary agricultural commodity in this region, reveals an underutilized surplus of nutmeg flesh, leading to organic waste accumulation. In response to the urgent need for minimizing organic waste and elevating the economic viability of nutmeg fruit flesh, this endeavor is driven by the realization that this waste represents an overlooked potential. Nutmeg flesh possesses intrinsic qualities, notably a rich concentration of antioxidants known for their role in promoting skin health, stabilizing cardiac rhythms, mitigating insomnia, alleviating angina, enhancing digestive processes, improving blood circulation, increasing appetite, and fortifying the immune system. The proposed solution involves the creation of nutmeg-flavored tea, intended to mitigate the issue of excess nutmeg fruit waste while simultaneously augmenting the economic worth of the produced merchandise. Thus, this initiative materializes as a strategy to optimize nutmeg fruit utilization, curtail waste generation, and amplify its market value. The Community Partnership Program administered by the ITERA team serves as a conduit for the enrichment of knowledge, insights, and competencies among local nutmeg farmers, empowering them to generate high-value commodities from an underexploited resource. The scope of activities encompasses the entire production process, extending to packaging design.